Adoption of Improved Tomato Cultivation Practices (Indian Journal of Extension Education, 2013)
Tomato is one of the major vegetable crops which can supplement the food needs of the country in a substantial way as it has achieved tremendous popularity over the last century. Tomato production in India has made tremendous progress with the development of new technologies. Due to the complexity in different technologies, sometimes farmers find it difficult to understand and they lag behind in the adoption of recommended package of practices. In this context, the need was felt to study the extent of adoption of tomato cultivation practices. An interview schedule was prepared to collect the data from 160 vegetable growers from Punjab. Recommended seed varieties of tomato were adopted by 65.00 per cent of respondents, whereas recommended dose of fertilizers were used by 58.00 per cent of respondents. Nearly half of the respondents used recommended insecticides/pesticides, fungicides and storage practices. The data further revealed that majority of the respondents had low extent of adoption of recommended cultivation practices of tomato crop. The data generated through this study can form the basis for planning integrated extension strategies to create more knowledge and awareness among the vegetable growers about the recommended cultivation practices of tomato crop.